2016
DOI: 10.1007/s12088-016-0594-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Investigation of Photorhabdus Bacteria for Nematode-Host Specificity

Abstract: Majority of animals form symbiotic relationships with bacteria. Based on the number of bacterial species associating with an animal, these symbiotic associations can be mono-specific, relatively simple (2-25 bacterial species/ animal) or highly complex ([10 2 -10 3 bacterial species/animal). Photorhabdus (family-Enterobacteriaceae) forms a mono-specific symbiotic relationship with the entomopathogenic nematode Heterorhabditis. This system provides a tractable genetic model for animal-microbe symbiosis studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In order to answer this question, the genetic variance of the toxins, and whether this variance can make a toxin protein hyper-or hypotoxic must be investigated in addition to the toxin expression patterns. Our study identified Photorhabdus 'virulence contrasts' which may be genetically probed using genomic or proteomic approaches to answer these questions, as was done for determining host specificity using proteomics approach [22]. In summary, we discovered a highly virulent strain of P. luminescens ssp.…”
mentioning
confidence: 94%
“…In order to answer this question, the genetic variance of the toxins, and whether this variance can make a toxin protein hyper-or hypotoxic must be investigated in addition to the toxin expression patterns. Our study identified Photorhabdus 'virulence contrasts' which may be genetically probed using genomic or proteomic approaches to answer these questions, as was done for determining host specificity using proteomics approach [22]. In summary, we discovered a highly virulent strain of P. luminescens ssp.…”
mentioning
confidence: 94%